Identification of a Golgi apparatus protein complex important for the asexual erythrocytic cycle of the malaria parasite Plasmodium falciparum - Hallée, Stéphanie; Kehrer, Jessica; Frischknecht, Friedrich; Mair, Gunnar R. (Cellular microbiology, 2018)
Compared with other eukaryotic cell types, malaria parasites appear to possess a more rudimentary Golgi apparatus being composed of dispersed, unstacked cis and trans-cisternae. Despite playing a central role in the secretory pathway of the parasite, few Plasmodium Golgi resident proteins have been characterised. We had previously identified a new Golgi resident protein of unknown function, which we had named Golgi Protein 1, and now show that it forms a complex with a previously uncharacterised transmembrane protein (Golgi Protein 2, GP2). The Golgi Protein complex localises to the cis-Golgi throughout the erythrocytic cycle and potentially also during the mosquito stages. Analysis of parasite strains where GP1 expression is conditionally repressed and/or the GP2 gene is inactivated reveals that though the Golgi protein complex is not essential at any stage of the parasite life cycle, it is important for optimal asexual development in the blood stages.